Pengaruh Model Budidaya terhadap Pertumbuhan dan Hasil Beberapa Varietas Jagung di Lahan Sulfat Masam - emelda, emelda; Dr.Ir. H. radian MS, Dr.Ir. H. radian MS; Maulidi, M. Sc, Maulidi, M. Sc (Jurnal Sains Mahasiswa Pertanian, 2016)
Acid sulphate soil has potential and prospect in agricultural development for the future to support the improvement of food security. Corn is one of food cop tahat is important to be cultivated in that land. The development of farming system and agribusiness of corn in swamp land shows good perspective, when it consider water management and soil improvement. This study aims to determine the best growth and yield of corn varieties best on some models of cultivation. This study was conducted at the village of Punggur Besar,district of Sungai Kakap provience Kubu Raya using the Split Blok Design that consised of two factors. Themodels of cultivation (Saturated Cultivation System = SBJA) as the main plot consisted of 4 levels: S1 (SBJA 40 cm - dolomite), S2 (SBJA 40 cm + dolomite), S3 (SBJA 30 cm - dolomite) and S4 (SBJA 30 cm + dolomite); and varieties as the subplot consised of 3 levels: Pionir31, Sukmaraga, and ST201341. The variables were observed in the study leaf length, dry weight of arial patsof plant, time of harvesting, and cob weight. The results showed the model of cultivation of the best on the growth and yield of corn are in the treatment of the culture system water-saturated groundwater levels 40 cm below the soil surface with the provision of lime , corn varieties showed growth and the best results in the area of acid sulphate are varieties of Pioneer 31 and the interaction between culture system saturated with water depth of 40 cm below the soil surface with varieties of lime on Pioneer 31 indicates growth and the best results in acid sulfate soil .